Effect of Pre-sowing Seed Treatments on Dormancy of Sunn hemp (Crotalaria juncea) - S RAJENDRAPRASAD; PMASILAMANI; K BALAKRISHNAN (Seed Research, 2026)
An experiment was conducted to find out the influence of presowing treatments on viability, germination and initial seedling vigour of freshly harvested sunn hemp (Crotalaria juncea L.) seeds. The seeds were subjected to pre-sowing treatments viz.; hot water soaking at 50°C, 60°C and 70°C for 8 hours, sand scarification for 5, 10 and 15 min, Acid scarification (H₂SO₄ @100 ml/kg) for 5, 10, 15 and 20 min, soaking in 1% and 2% of CaOCl₂ and H₂O₂ for 8 hrs and dry seed served as the control. Treated seeds were tested for seed quality under in vitro conditions. The results revealed that the seeds treated with hot water (70°C) for 8 hours had broken the seed coat dormancy without affecting the viability of seeds thus reduced the hard seed from 33 per cent to 2 per cent and also improved the germination (89%), shoot length (19.2 cm) and vigour index (3185).